2022
DOI: 10.3389/fpsyt.2022.832139
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on Sexuality and Sexual Experiences in Community Forensic Mental Health Patients in Queensland, Australia

Abstract: This qualitative study reports on the sexuality and sexual experiences of community-based forensic mental health participants. The findings indicate that these participants feel the need for intimacy and want to engage in sexual activity more often than their neurotypical Australian peers. Participants identified their mental health and the side effects of compliance with prescribed psychotropic medications were barriers to achieving their desired level of sexual activity. Participants supported the notion tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…This finding was supported by both Ravenhill et al ( 34 ) and Hales et al ( 29 ) who point out that forensic patients experience sexual feelings, sexual desires, interests and hopes for current and future sexual experiences and relationships. Further evidence of the “normality” of sex was reported by Brand et al ( 35 ) with 12 out of 14 community forensic mental health patients describing a desire for sex with a regular partner. Their desired ideal of sexual intimacy ranged from having sex at least twice per week to having sex daily (an average of 3.71 times per week).…”
Section: Synthesis Of Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…This finding was supported by both Ravenhill et al ( 34 ) and Hales et al ( 29 ) who point out that forensic patients experience sexual feelings, sexual desires, interests and hopes for current and future sexual experiences and relationships. Further evidence of the “normality” of sex was reported by Brand et al ( 35 ) with 12 out of 14 community forensic mental health patients describing a desire for sex with a regular partner. Their desired ideal of sexual intimacy ranged from having sex at least twice per week to having sex daily (an average of 3.71 times per week).…”
Section: Synthesis Of Resultsmentioning
confidence: 80%
“…Despite the longevity of hospitalization, Ravenhill et al ( 34 ), reported that patients maintain their pre-admission sexual orientation. According to Brown et al ( 2 ), and further illustrated Brand et al ( 35 ), Brand ( 36 ) active positive and negative symptoms of SMI, and significant sexual side effects of psychotropic medication further amplify sexual difficulties and negative sexual experiences.…”
Section: Synthesis Of Resultsmentioning
confidence: 96%
See 3 more Smart Citations